High doses of CRISPR/Cas9 ribonucleoprotein efficiently induce gene knockout with low mosaicism in the hydrozoan Clytia hemisphaerica through microhomology-mediated deletion - Momose, Tsuyoshi (Sci Rep, 2018)
Targeted mutagenesis using CRISPR/Cas9 technology has been shown to be a powerful approach to examine gene function in diverse metazoan species. One common drawback is that mixed genotypes, and thus variable phenotypes, arise in the F0 generation because incorrect DNA repair produces different mutations amongst cells of the developing embryo. We report here an effective method for gene knockout (KO) in the hydrozoan Clytia hemisphaerica, by injection into the egg of Cas9/sgRNA ribonucleoprotein complex (RNP). Expected phenotypes were observed in the F0 generation when targeting endogenous GFP genes, which abolished fluorescence in embryos, or CheRfx123 (that codes for a conserved master transcriptional regulator for ciliogenesis) which caused sperm motility defects. When high concentrations of Cas9 RNP were used, the mutations in target genes at F0 polyp or jellyfish stages were not random but consisted predominantly of one or two specific deletions between pairs of short microhomologies flanking the cleavage site. Such microhomology-mediated (MM) deletion is most likely caused by microhomology-mediated end-joining (MMEJ), which may be favoured in early stage embryos. This finding makes it very easy to isolate uniform, largely non-mosaic mutants with predictable genotypes in the F0 generation in Clytia, allowing rapid and reliable phenotype assessment.